Study of substrate‐free microporous layer of proton exchange membrane fuel cells. (15th March 2022) - Wang, Manli; Hou, Ming; Gao, Yanyan; Chen, Haiping; Lv, Bo; Song, Wei; Shao, Zhigang
Summary: The gas diffusion layer (GDL) is a vital constituent of proton exchange membrane fuel cells (PEMFCs), which directly affects the performance and cost of PEMFCs. Also, the GDL integration can simplify the structure of PEMFC. Herein, a novel substrate‐free microporous layer (sfMPL) has been successfully prepared by a dry‐press method, which broadens the usable humidity range of PEMFCs and improves the performance under different humidity conditions. Precisely, the maximum power density of a single‐cell assembled by sfMPL (with optimised 10 wt.% binder content and 1.0 g pore‐forming agent) is 754 mW cm −2 at 40% relative humidity, which is 36.6% higher than that with conventional GDL (552 mW cm −2 ). Furthermore, the sfMPL shows outstanding stability after high potential oxidation (1.6 V vs RHE). Our results highlight a promising new class of low‐cost, substrate‐free MPL for PEMFCs and provide a basis for future research on substrate‐free MPL. Abstract : sfMPL is prepared by a dry‐press method with the advantages of operational simplicity, solvent‐free, and excellent reproducibility. Benefiting from a suitable pore size distribution, sfMPL broadens the useable humidity range for PEMFC. The optimized sfMPL‐2 delivered improved single‐cell performance compared with C‐GDL at all humidity ranges.